Case Report: Clinical Outcome From Pallidal Stimulation in a Patient With Levodopa-Resistant Dopa-Responsive Dystonia - Wang, Xue; Mei, Shanshan; Tian, Zichen; Wang, Lin; Hao, Guiliang; Zhu, Xin; Mao, Wei; Li, Jianyu (Frontiers in Neurology, 2022)
Dopa-responsive dystonia (DRD) is a group of movement disorders with genetical and clinical heterogeneity. Dramatic response to levodopa is the hallmark of DRD. Therefore, DRD cases with poor response to levodopa are rarely reported. In addition, the clinical outcomes from deep brain stimulation (DBS) in levodopa resistant patients remain unclear. To fill this knowledge gap, here, we described the clinical outcome from pallidal stimulation in a DRD patient having a poor response to levodopa. The patient was a 25-year-old male and had a 7-year history of cervical dystonia. A novel frameshift mutation in the GCH1 gene was found in the patient as well as his elder sister and mother. Unfortunately, he had no response to large dosage of levodopa/benserazide (600/150mg per day) and onabotulinumtoxin A injection. Therefore, bilateral globus pallidus internus (GPi) deep brain stimulation (DBS) was performed. With parameter adjustments, the severity of his torticollis was gradually improved and relieved substantially in the 8-month follow-up visit. Our current report highlights that GPi-DBS therapy leads to promising clinical outcome for levodopa-resistant DRD.